2007
DOI: 10.2169/internalmedicine.46.6053
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Pyogenic Vertebral Osteomyelitis

Abstract: Objective Early diagnosis of pyogenic vertebral osteomyelitis (PVO) is frequently difficult. There are, however, few studies that have investigated the diagnostic performance of PVO in Japan. Our aim was to analyze the diagnostic performance and identify clinical factors associated with the diagnostic delay of PVO. Materials and Methods We performed hospital-based retrospective case analysis. All patients with PVO were identified from the computerized medical database at Okinawa Chubu Hospital in Okinawa, Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…9,10 Spinal infections are relatively uncommon, with incidence approximating 0.2-3.7/100 000 for spondylodiscitis and 2-20/100 000 hospital admissions for spinal epidural abscesses. 8,9,21 Relatively few spinal infection studies specifically deal with older populations. 1,10,11,[13][14][15] Delayed or missed diagnosis results in poorer outcomes, including significant morbidity, mortality and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Spinal infections are relatively uncommon, with incidence approximating 0.2-3.7/100 000 for spondylodiscitis and 2-20/100 000 hospital admissions for spinal epidural abscesses. 8,9,21 Relatively few spinal infection studies specifically deal with older populations. 1,10,11,[13][14][15] Delayed or missed diagnosis results in poorer outcomes, including significant morbidity, mortality and functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical assessment may be difficult because of pre-existing cognitive impairment or intercurrent delirium, as well as atypical or subtler signs, symptoms and biochemical marker abnormalities. 8,9,21 Relatively few spinal infection studies specifically deal with older populations. 8,20,22,23 Data on spinal infections in Australasia are similarly sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical diagnosis of vertebral osteomyelitis is challenging; a long duration from the onset of symptoms to admission (average, 48±40 days) and very high incidence of initial misdiagnosis (80%) have been reported [ 7 ]. The lack of specific symptoms and low sensitivity of diagnostic tests seem to be associated with these diagnostic delays and misdiagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite suspicion that vertebral osteomyelitis was improbable in this case since vertebral osteomyelitis following osteoporotic vertebral fracture is reported to be very rare [ 19 ], physicians should consider that a working diagnosis of UTI may be an indicator to continue diagnostic workup. A previous study reported that UTI was the most common initial misdiagnosis in patients with vertebral osteomyelitis [ 7 ]. Pyuria, despite being considered evidence of UTI, is not always an accurate diagnostic marker for it.…”
Section: Discussionmentioning
confidence: 99%
“…There is often a considerable delay between the onset of symptoms and diagnosis (a range of 42 to 59 days in five studies) [7][8][9][10] . The reported median of the total duration to the diagnosis was 19 days 6) . In one study, the initial misdiagnosis rate was 34% with an average delayed diagnosis time of 2.6 months 11) .…”
Section: Discussionmentioning
confidence: 99%